Demographic and substance use factors associated with non-violent alcohol-related injuries among patrons of Australian night-time entertainment districts - Coomber, K.; Mayshak, R.; Hyder, S.; Droste, N.; Curtis, A.; Pennay, A.; Gilmore, William; Lam, Tina; Chikritzhs, Tanya; Miller, Peter (Molecular Diversity Preservation International (MDPI), 2017)
© 2017 by the authors; licensee MDPI, Basel, Switzerland.This study examined the relationship between patron demographics, substance use, and experience of recent alcohol-related accidents and injuries that were not due to interpersonal violence in night-time entertainment districts. Cross-sectional interviews (n = 4016) were conducted around licensed venues in entertainment districts of five Australian cities. Demographic factors associated with non-violent alcohol-related injuries were examined, including gender, age, and occupation. The association between substance use on the night of interview; blood alcohol concentration (BAC), pre-drinking, energy drink consumption, and illicit drug use; and experience of injury was also explored. Thirteen percent of participants reported an alcohol-related injury within the past three months. Respondents aged younger than 25 years were significantly more likely to report an alcohol-related injury. Further, a significant occupation effect was found indicating the rate of alcohol-related injury was lower in managers/professionals compared to non-office workers. The likelihood of prior alcohol-related injury significantly increased with BAC, and self-reported pre-drinking, energy drink, or illicit drug consumption on the night of interview. These findings provide an indication of the demographic and substance use-related associations with alcohol-related injuries and, therefore, potential avenues of population-level policy intervention. Policy responses to alcohol-related harm must also account for an assessment and costing of non-violent injuries.